Problems of Lithuanian olympiad’08 - Mačys, Juozas Juvencijus (Lietuvos matematikos rinkinys, 2008)
The problems of the Lithuanian mathematical school olympiad-2008are presentedand solutions are given.
Keywords: mathematical olympiads; problems solving